Adhesive for stone board composite and preparation method and application thereof
By using two-component epoxy resin adhesive, the raw material usage of components A and B is optimized, and the existing adhesives are easily delaminated, have high viscosity, difficult to apply and long curing time, and high bond strength is achieved , easy to apply and suitable curing time, improves the processing efficiency of stone board composite and reduces production costs.
Patent Information
- Application Number
- CN202211686101.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-27
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-12-27
AI Technical Summary
The existing adhesives used for stone board composites are easy to delaminate, have high viscosity, are difficult to apply, are inconvenient to use, and have a long curing time, which affects processing efficiency and increases production costs.
Two-component epoxy resin adhesive is used, component A includes epoxy resin, polyether polyol, diluent, barium sulfate and white carbon black, component B includes polyether amine, modified amine curing agent, additive, sulfuric acid Barium and white carbon black, by optimizing the amount of each raw material, ensure that the A glue and B glue are not layered. The adhesive formed after mixing is easy to apply and use, and the curing time is moderate.
The adhesive has achieved high bonding strength, no layering, easy to apply, easy to use and moderate curing time, which improves the processing efficiency of stone board composite and reduces production costs.
Smart Images

Figure BDA0004021226080000011 
Figure BDA0004021226080000012 
Figure BDA0004021226080000031
Abstract
Description
Technical Field
[0001] The invention relates to an adhesive for stone plate composite and a preparation method and application thereof. Background Art
[0002] Compared with stone adhesives in the construction field, the stone processing field has put forward higher requirements on the performance of adhesives, such as requiring the adhesive liquid and powder to be non-stratified, and requiring the adhesive to be easier to apply. However, most of the adhesives currently available on the market for stone slab composites are prone to stratification, which is difficult to meet the requirements, and have high viscosity, difficult to apply, and inconvenient to use. In addition, the existing adhesives used for stone composites have defects such as long curing time, which is not conducive to improving processing efficiency and reducing costs. Therefore, obtaining an adhesive suitable for stone slab composites that is non-stratified, easy to apply, easy to use, and has a moderate curing time is of great significance for preparing high-quality stone composite panels and improving processing efficiency and reducing production costs. Summary of the invention
[0003] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide an adhesive for stone slab composite which has high bonding strength, no delamination, is easy to apply, is convenient to use and has a moderate curing time, as well as a preparation method and application thereof.
[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0005] An adhesive for stone slab composite, comprising component A and component B;
[0006] The component A comprises the following raw material components in terms of weight percentage:
[0007]
[0008] The B component comprises the following raw material components in terms of weight percentage:
[0009]
[0010] The above adhesive is further improved, wherein the epoxy resin is bisphenol A epoxy resin, diluted bisphenol A epoxy resin or a mixture thereof; the mass ratio of bisphenol A epoxy resin to diluted bisphenol A epoxy resin in the mixture of bisphenol A epoxy resin and diluted bisphenol A epoxy resin is 1:1.
[0011] The above-mentioned adhesive is further improved, wherein the diluted bisphenol A epoxy resin is a mixture prepared by mixing bisphenol A epoxy resin with 501 epoxy resin diluent; the viscosity of the diluted bisphenol A epoxy resin is 1000mPa·s / 25℃~1300mPa·s / 25℃, and the epoxy equivalent is 148g / mol~155g / mol.
[0012] The above adhesive is further improved, wherein the diluent is at least one of C12-14 alcohol glycidyl ether, benzyl glycidyl ether, and benzyl alcohol.
[0013] The above adhesive is further improved, in the component A: the barium sulfate is active barium sulfate; the mesh size of the active barium sulfate is 1000 mesh to 1500 mesh; the white carbon black is at least one of fumed white carbon black and precipitated white carbon black.
[0014] The above adhesive is further improved, in which the modified amine curing agent in the B component is a modified alicyclic amine curing agent; the modified alicyclic amine curing agent is prepared by the following method: adding the alicyclic amine curing agent to the reactor, adjusting the temperature in the range of 30°C to 36°C, adding 501 epoxy resin diluent dropwise, completing the reaction in 3 hours, adjusting the temperature to 40°C to 50°C and continuing the reaction for 2 hours, filtering, discharging, and obtaining the modified alicyclic amine curing agent; the molar ratio of the alicyclic amine curing agent to the 501 epoxy resin diluent is 2:1; the alicyclic amine curing agent is isophoronediamine.
[0015] The above adhesive is further improved, in the B component: the auxiliary agent is at least one of benzyl alcohol and isobutyl alcohol; the barium sulfate is active barium sulfate; the mesh number of the active barium sulfate is 1000 mesh to 1500 mesh; the white carbon black is at least one of fumed white carbon black and precipitated white carbon black.
[0016] The above adhesive is further improved in that the weight ratio of component A to component B is 2:1.
[0017] As a general technical concept, the present invention also provides a method for preparing the above-mentioned adhesive, comprising the following steps:
[0018] S1. Heat the epoxy resin to 60° C. to 70° C., add polyether polyol and diluent, mix well, add white carbon black and barium sulfate in sequence, stir to obtain component A; in a reactor, add polyether amine, modified amine curing agent and auxiliary agent step by step, mix well, add white carbon black and barium sulfate step by step, stir to obtain component B;
[0019] S2. Mix component A and component B to obtain an adhesive.
[0020] As a general technical concept, the present invention also provides a use of the above-mentioned adhesive or the adhesive prepared by the above-mentioned preparation method in the preparation of stone composite panels.
[0021] Compared with the prior art, the advantages of the present invention are:
[0022] Aiming at the defects that most of the existing adhesives used for stone plate composite are easy to delaminate, have high viscosity, are difficult to apply and inconvenient to use, the present invention provides an adhesive for stone plate composite, which comprises epoxy resin, polyether polyol 400, diluent, barium sulfate and white carbon black as component A, and polyether amine D230, modified amine curing agent, auxiliary agent, barium sulfate and white carbon black as component B. By optimizing the amount of each raw material in component A and component B, neither adhesive A nor adhesive B is delaminated. Therefore, the adhesive obtained by mixing adhesive A and adhesive B can be directly used for stone plate bonding, which is not only convenient to operate but also has no delamination. At the same time, the adhesive has better application performance, which is conducive to reducing the difficulty of application and is more convenient to use. More importantly, the adhesive has a moderate curing time, and the performance after curing fully meets the bonding requirements, which is conducive to improving processing efficiency and reducing costs. In addition, by optimizing the amount of powder (such as barium sulfate, white carbon black), not only can the bonding strength of the adhesive be further increased, the brushing performance is better, and it is also conducive to further reducing costs. In addition, the adhesive of the present invention is colorless and transparent, which is conducive to avoiding the color of the adhesive itself from having an adverse effect on the quality of the stone. The adhesive of the present invention has the advantages of high bonding strength, no stratification, easy brushing, convenient use, and moderate curing time. It is a new type of epoxy resin adhesive with excellent performance, which can be widely used for effective bonding between stones and between stones and other materials, and can effectively overcome the adverse effects of the stone itself and environmental factors on curing. It has high use value and good application prospects. DETAILED DESCRIPTION
[0023] The present invention is further described below in conjunction with specific preferred embodiments, but the protection scope of the present invention is not limited thereby.
[0024] The raw materials and instruments used in the following examples are all commercially available; the equipment and preparation processes used are all conventional equipment and conventional processes unless otherwise specified.
[0025] Example 1
[0026] An adhesive for stone plate composite includes component A and component B, wherein component A includes the following raw material components in terms of weight percentage:
[0027]
[0028] Component B includes the following raw material components by weight percentage:
[0029]
[0030] In this embodiment, the polyether polyol 400 used has the smallest molecular weight, low viscosity and high reactivity, which are not available in other materials.
[0031] In this embodiment, the epoxy resin used is a mixture of bisphenol A epoxy resin and diluted bisphenol A epoxy resin, wherein the epoxy resin is a mixture of bisphenol A epoxy resin and diluted bisphenol A epoxy resin in a mass ratio of 1:1, wherein the diluted bisphenol A epoxy resin is a mixture prepared by mixing bisphenol A epoxy resin with 501 epoxy resin diluent; the viscosity of the diluted bisphenol A epoxy resin is 1200mPa·s / 25°C, and the epoxy equivalent is 150g / mol.
[0032] In this embodiment, the diluent used is benzyl alcohol.
[0033] In this embodiment, in component A, the barium sulfate is active barium sulfate, wherein the mesh number of the active barium sulfate is 1250 meshes.
[0034] In this embodiment, in component A, the white carbon black is fumed white carbon black.
[0035] In this embodiment, in component B: the modified amine curing agent is a modified alicyclic amine curing agent, wherein the modified alicyclic amine curing agent is prepared by the following method: adding the alicyclic amine curing agent to the reactor, adjusting the temperature in the range of 30°C to 36°C, dripping 501 epoxy resin diluent, completing in 3 hours, adjusting the temperature to 40°C to 50°C and continuing the reaction for 2 hours, filtering, discharging, and obtaining the modified alicyclic amine curing agent, the molar ratio of the alicyclic amine curing agent to the 501 epoxy resin diluent is 2:1, and the alicyclic amine curing agent is isophorone diamine. In the present invention, the 501 epoxy resin diluent used has a small molecular weight and low viscosity, and is therefore more conducive to preparing a curing agent with a small viscosity, and is easier to meet the requirements, which is not available and cannot be obtained when 622 is used as a diluent.
[0036] In this embodiment, in component B: the polyetheramine is polyetheramine D230.
[0037] In this embodiment, in component B: the barium sulfate is active barium sulfate, wherein the mesh number of the active barium sulfate is 1250 meshes.
[0038] In this embodiment, in component B, the white carbon black is fumed white carbon black.
[0039] In this embodiment, the weight ratio of component A to component B is 2:1.
[0040] A method for preparing the adhesive for stone slab composite in the above embodiment comprises the following steps:
[0041] Heat 40.0g of epoxy resin to 60-70°C and add it into a mixing container, add 15.0g of polyether polyol 400 and 6.0g of diluent, mix well, add 1.0g of white carbon black and 38.0g of barium sulfate step by step, disperse them evenly by high-speed dispersion, and prepare component A.
[0042] 30.0 g of polyetheramine D230 curing agent, 10.0 g of modified alicyclic amine curing agent and 4.0 g of auxiliary agent were added into a mixing container in sequence and mixed evenly. 1.0 g of white carbon black and 55.0 g of barium sulfate were added step by step and dispersed evenly by high-speed dispersion to obtain component B.
[0043] Component A and component B are mixed in a weight ratio of 2:1, and after being evenly mixed, an adhesive for stone slab composite is obtained, which can be used directly.
[0044] An application of the adhesive for stone board composite in the above embodiment in preparing a stone composite board is specifically to apply the adhesive for stone board composite between two pieces of stone to prepare a stone composite board.
[0045] The properties of the adhesive for stone board composite in this embodiment are shown in Table 1. In addition, the stone composite board prepared in this embodiment is placed at a temperature of 25°C for curing, and the results are shown in Table 1. The results show that the adhesive for stone board composite of the present invention has a moderate curing time, and the performance after curing meets the requirements of stone composite adhesive, and has the advantages of high bonding strength, no delamination, good brushing performance, easy use, low shrinkage, etc. It is a new type of epoxy resin adhesive with excellent performance, and the composite production requirements of the stone composite board after curing are met, the processing efficiency is high, and the production cost is lower.
[0046] Example 2
[0047] An adhesive for stone plate composite includes component A and component B, wherein component A includes the following raw material components in terms of weight percentage:
[0048]
[0049] Component B includes the following raw material components by weight percentage:
[0050]
[0051] In this embodiment, the epoxy resin used is a mixture of bisphenol A epoxy resin and diluted bisphenol A epoxy resin, wherein the epoxy resin is a mixture of bisphenol A epoxy resin and diluted bisphenol A epoxy resin in a mass ratio of 1:1, wherein the diluted bisphenol A epoxy resin is a mixture prepared by mixing bisphenol A epoxy resin with 501 epoxy resin diluent; the viscosity of the diluted bisphenol A epoxy resin is 1200mPa·s / 25°C, and the epoxy equivalent is 150g / mol.
[0052] In this embodiment, the diluent used is benzyl glycidyl ether.
[0053] In this embodiment, in component A, the barium sulfate is active barium sulfate, wherein the mesh number of the active barium sulfate is 1000 mesh.
[0054] In this embodiment, in component A, the white carbon black is fumed white carbon black.
[0055] In this embodiment, in component B: the modified amine curing agent is a modified alicyclic amine curing agent, wherein the modified alicyclic amine curing agent is prepared by the following method: adding the alicyclic amine curing agent into the reactor, adjusting the temperature in the range of 30°C to 36°C, adding 501 epoxy resin diluent dropwise, completing the reaction in 3 hours, adjusting the temperature to 40°C to 50°C and continuing the reaction for 2 hours, filtering, discharging, and obtaining the modified alicyclic amine curing agent, the molar ratio of the alicyclic amine curing agent to the 501 epoxy resin diluent is 2:1, and the alicyclic amine curing agent is isophoronediamine.
[0056] In this embodiment, in component B, the barium sulfate is active barium sulfate, wherein the mesh number of the active barium sulfate is 1000 mesh.
[0057] In this embodiment, in component B, the white carbon black is fumed white carbon black.
[0058] In this embodiment, the weight ratio of component A to component B is 2:1.
[0059] A method for preparing the adhesive for stone slab composite in the above embodiment comprises the following steps:
[0060] Heat 50.0g of epoxy resin to 60-70°C and add it into a mixing container, add 11.0g of polyether polyol 400 and 8.0g of diluent, mix well, add 1.0g of white carbon black and 30.0g of barium sulfate step by step, disperse them evenly by high-speed dispersion, and prepare component A.
[0061] 37.0 g of polyetheramine D230 curing agent, 15.0 g of modified alicyclic amine curing agent and 6.0 g of auxiliary agent were added into a mixing container in sequence and mixed evenly. 2.0 g of white carbon black and 40.0 g of barium sulfate were added step by step and dispersed evenly by high-speed dispersion to obtain component B.
[0062] Component A and component B are mixed in a weight ratio of 2:1, and after being evenly mixed, an adhesive for stone slab composite is obtained, which can be used directly.
[0063] An application of the adhesive for stone board composite in the above embodiment in preparing a stone composite board is specifically to apply the adhesive for stone board composite between two pieces of stone to prepare a stone composite board.
[0064] The properties of the adhesive for stone board composite in this embodiment are shown in Table 1. In addition, the stone composite board prepared in this embodiment is placed at a temperature of 25°C for curing, and the results are shown in Table 1. The results show that the adhesive for stone board composite of the present invention has a moderate curing time, and the performance after curing meets the requirements of stone composite adhesive, and has the advantages of high bonding strength, no delamination, good brushing performance, easy use, low shrinkage, etc. It is a new type of epoxy resin adhesive with excellent performance, and the composite production requirements of the stone composite board after curing are met, the processing efficiency is high, and the production cost is lower.
[0065] Example 3
[0066] An adhesive for stone plate composite includes component A and component B, wherein component A includes the following raw material components in terms of weight percentage:
[0067]
[0068] Component B includes the following raw material components by weight percentage:
[0069]
[0070] In this embodiment, the epoxy resin used is a mixture of bisphenol A epoxy resin and diluted bisphenol A epoxy resin, wherein the epoxy resin is a mixture of bisphenol A epoxy resin and diluted bisphenol A epoxy resin in a mass ratio of 1:1, wherein the diluted bisphenol A epoxy resin is a mixture prepared by mixing bisphenol A epoxy resin with 501 epoxy resin diluent; the viscosity of the diluted bisphenol A epoxy resin is 1200mPa·s / 25°C, and the epoxy equivalent is 150g / mol.
[0071] In this embodiment, the diluent used is benzyl glycidyl ether.
[0072] In this embodiment, in component A, the barium sulfate is active barium sulfate, wherein the mesh number of the active barium sulfate is 1500 meshes.
[0073] In this embodiment, in component A, the white carbon black is fumed white carbon black.
[0074] In this embodiment, in component B: the modified amine curing agent is a modified alicyclic amine curing agent, wherein the modified alicyclic amine curing agent is prepared by the following method: adding the alicyclic amine curing agent into the reactor, adjusting the temperature in the range of 30°C to 36°C, adding 501 epoxy resin diluent dropwise, completing the reaction in 3 hours, adjusting the temperature to 40°C to 50°C and continuing the reaction for 2 hours, filtering, discharging, and obtaining the modified alicyclic amine curing agent, the molar ratio of the alicyclic amine curing agent to the 501 epoxy resin diluent is 2:1, and the alicyclic amine curing agent is isophoronediamine.
[0075] In this embodiment, in component B: the barium sulfate is active barium sulfate, wherein the mesh number of the active barium sulfate is 1500 meshes.
[0076] In this embodiment, in component B, the white carbon black is fumed white carbon black.
[0077] In this embodiment, the weight ratio of component A to component B is 2:1.
[0078] A method for preparing the adhesive for stone slab composite in the above embodiment comprises the following steps:
[0079] Heat 44.0g of epoxy resin to 60-70°C and add it into a mixing container, add 14.0g of polyether polyol 400 and 7.0g of diluent, mix well, add 1.2g of white carbon black and 33.8g of barium sulfate step by step, and disperse them evenly using a high-speed disperser to obtain component A.
[0080] 35.0 g of polyetheramine D230 curing agent, 12.0 g of homemade modified alicyclic amine curing agent and 5.0 g of auxiliary agent were added to a mixing container in sequence and mixed evenly. 1.3 g of white carbon black and 46.7 g of barium sulfate were added step by step and dispersed evenly by high-speed dispersion to obtain component B.
[0081] Component A and component B are mixed in a weight ratio of 2:1, and after being evenly mixed, an adhesive for stone slab composite is obtained, which can be used directly.
[0082] An application of the adhesive for stone board composite in the above embodiment in preparing a stone composite board is specifically to apply the adhesive for stone board composite between two pieces of stone to prepare a stone composite board.
[0083] The properties of the adhesive for stone board composite in this embodiment are shown in Table 1. In addition, the stone composite board prepared in this embodiment is placed at a temperature of 25°C for curing, and the results are shown in Table 1. The results show that the adhesive for stone board composite of the present invention has a moderate curing time, and the performance after curing meets the requirements of stone composite adhesive, and has the advantages of high bonding strength, no delamination, good brushing performance, easy use, low shrinkage, etc. It is a new type of epoxy resin adhesive with excellent performance, and the composite production requirements of the stone composite board after curing are met, the processing efficiency is high, and the production cost is lower.
[0084] Comparative Example 1
[0085] An adhesive is substantially the same as Example 3, except that: in the adhesive of Reference Document 1, component A comprises the following raw material components by weight percentage:
[0086]
[0087]
[0088] The adhesive of Comparative Example 1 was coated between two pieces of stone to produce a stone composite board.
[0089] The properties of the adhesive in Comparative Example 1 are shown in Table 1. In addition, the stone composite board prepared in Comparative Example 1 was placed at a temperature of 25°C for curing, and the results are shown in Table 1. The results show that when the adhesive in Comparative Example 1 is used to bond stone, it is easy to delaminate, has poor brushing performance, takes a long time to cure, and has poor strength.
[0090] Comparative Example 2
[0091] An adhesive is substantially the same as Example 3, except that: in the adhesive of Reference Document 3, component A comprises the following raw material components by weight percentage:
[0092]
[0093] The adhesive of Comparative Example 2 was coated between two pieces of stone to produce a stone composite board.
[0094] The properties of the adhesive in Comparative Example 2 are shown in Table 1. In addition, the stone composite board prepared in Comparative Example 2 was placed at a temperature of 25°C for curing, and the results are shown in Table 1. The results show that when the adhesive in Comparative Example 2 is used to bond stone, it is easy to delaminate, has poor brushing performance, takes a long time to cure, and has poor strength.
[0095] Table 1 Performance comparison of different two-component epoxy resin composite adhesives and stone composite panels
[0096]
[0097] The above embodiments are only preferred implementations of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. An adhesive for stone board composite, characterized in that: It includes component A and component B; The component A comprises the following raw material components in terms of weight percentage: Epoxy resin 40%~52%, Polyether polyol 400 11%~16%, Diluent 6%~10%, Barium sulfate 29%~39%, White carbon black 1% to 2.0%, and the sum of the weight percentages of each raw material is 100%; The B component comprises the following raw material components in terms of weight percentage: Polyetheramine D230 30%~40%, Modified amine curing agent 10%~16%, Additives 4% to 6%, Barium sulfate 40%~55%, White carbon black 1% to 2.0%, and the sum of the weight percentages of each raw material is 100%; The epoxy resin is a mixture of bisphenol A epoxy resin and diluted bisphenol A epoxy resin; the mass ratio of the bisphenol A epoxy resin to the diluted bisphenol A epoxy resin is 1:1; The diluted bisphenol A epoxy resin is a mixture prepared by mixing bisphenol A epoxy resin and 501 epoxy resin diluent; the viscosity of the diluted bisphenol A epoxy resin is 1000 mPa·s / 25°C to 1300 mPa·s / 25°C, and the epoxy equivalent is 148 g / mol to 155 g / mol; The modified amine curing agent is a modified alicyclic amine curing agent; the modified alicyclic amine curing agent is prepared by the following method: adding the alicyclic amine curing agent into a reactor, adjusting the temperature in the range of 30°C to 36°C, dripping 501 epoxy resin diluent, completing the reaction in 3 hours, adjusting the temperature to 40°C to 50°C and continuing the reaction for 2 hours, filtering, discharging, and obtaining the modified alicyclic amine curing agent.
2. The adhesive according to claim 1, characterized in that The diluent is at least one of C12-14 alcohol glycidyl ether, benzyl glycidyl ether and benzyl alcohol.
3. The adhesive according to claim 1, characterized in that In the component A, the barium sulfate is active barium sulfate; the mesh size of the active barium sulfate is 1000-1500 mesh; the white carbon black is at least one of fumed white carbon black and precipitated white carbon black.
4. The adhesive according to any one of claims 1 to 3, characterized in that The molar ratio of the alicyclic amine curing agent to the 501 epoxy resin diluent is 2:1; the alicyclic amine curing agent is isophorone diamine.
5. The adhesive according to any one of claims 1 to 3, characterized in that In the B component: the auxiliary agent is at least one of benzyl alcohol and isobutyl alcohol; the barium sulfate is active barium sulfate; the mesh number of the active barium sulfate is 1000 mesh to 1500 mesh; the white carbon black is at least one of fumed white carbon black and precipitated white carbon black.
6. The adhesive according to any one of claims 1 to 3, characterized in that The weight ratio of the component A to the component B is 2:
1.
7. A method for preparing the adhesive according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Heat the epoxy resin to 60° C. to 70° C., add polyether polyol and diluent, mix well, add white carbon black and barium sulfate in sequence, stir to obtain component A; in a reactor, add polyether amine, modified amine curing agent and auxiliary agent step by step, mix well, add white carbon black and barium sulfate step by step, stir to obtain component B; S2. Mix component A and component B to obtain an adhesive.
8. Use of the adhesive according to any one of claims 1 to 6 or the adhesive prepared by the preparation method according to claim 7 in preparing a stone composite board.
Citation Information
Patent Citations
Epoxy resin adhesive and preparation method thereof
CN104312508A
Novel epoxy resin sealant adhesive and preparation method thereof
CN104559892A